Giorgio Agamben, creazione e anarchia. L’opera Nell’età della religione capitalista, neri pozza, Vicenza 2017, p. 140, € 12.50, isbn 9788854515604 - Junges, Márcia Rosane (Veritas (Porto Alegre), 2019)
—